2010
DOI: 10.1007/s00508-010-1480-4
|View full text |Cite
|
Sign up to set email alerts
|

An uncommon cause of anaemia: Sheehan's syndrome

Abstract: Ischemic pituitary necrosis due to severe postpartum haemorrhage called Sheehan's syndrome is a rare cause of hypopituitarism in the western world, but much more common in developing countries. A 45-year-old female patient being a war refugee from Chechnya with severe anaemia and fatigue was diagnosed at our outpatient department with Sheehan's syndrome after severe postpartum haemorrhage and emergency hysterectomy 15 years ago. Panhypopituitarism was adequately treated with substitution of hydrocortisone, thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…Similar to what occurred to our patient, there have been reports of individuals that were submitted to longstanding clinical treatment for chronic anemia, which never resolved, before actually being diagnosed with Sheehan's syndrome [14][15][16][17]. Gokalp et al, in 2009, showed that 80% of the studied population with this syndrome suffered from anemia.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to what occurred to our patient, there have been reports of individuals that were submitted to longstanding clinical treatment for chronic anemia, which never resolved, before actually being diagnosed with Sheehan's syndrome [14][15][16][17]. Gokalp et al, in 2009, showed that 80% of the studied population with this syndrome suffered from anemia.…”
Section: Discussionsupporting
confidence: 84%
“…This is a 30-year-old woman, who presents an SS diagnosed 6 years after a hemorrhage of delivery, complicated by a deep vein thrombosis of the left poplitea. The only biological abnormality highlighted was normochromic normocytic anemia [11]. In their prospective study of 121 patients, Stolz et al, confirm the significant association between severe anemia and cerebral venous thrombosis [12].…”
Section: Discussionmentioning
confidence: 94%
“…Le diagnostic de SS est le plus souvent tardif ; dans 50 % des cas, il n'est porté que dix ans après l'événement obsté-trical, devant l'apparition tardive des signes classiques d'insuffisance hypophysaire (amaigrissement, asthénie, ané-mie, hypotension artérielle, aménorrhée secondaire) [2][3][4] ; le seul signe précoce, qui est malheureusement souvent négligé, est l'absence de montée laiteuse témoignant du défi-cit de la lignée lactotrope.…”
Section: Introductionunclassified